Antibody-based alternatives to animal testing for toxin detection and antitoxin evaluation - Chang, Seo-Hyuk; Jang, Jieun; Yang, Wonjun; Lee, Nam-Kyung; Choi, Seoyeon; Jung, Hyo-Il; Kim, Wantae; Cha, Boksik; Yoon, Sung-Jin; Noh, Ji-Yoon; Lee, Jangwook (Frontiers in Toxicology, 2025)
Animal experiments have long played a central role in biomedical research and toxicology, yet their limitations in translational accuracy and ethical concerns have intensified the demand for reliable alternatives. Antibody-based technologies are versatile tools used to develop non-animal testing methods capable of detecting toxins and evaluating antitoxins. Enzyme-linked immunosorbent assay and lateral flow assays, among other techniques, have demonstrated high specificity, sensitivity, and reproducibility and are useful in diagnostics, therapeutic development, and as platforms to replace traditional animal assays. Recent developments in in vitro systems, including organoids and microphysiological systems, as well as the integration of AI-based in silico models, offer promising directions. Standardization and regulatory acceptance remain key challenges. A coordinated approach can facilitate the development of antibody-based systems to fulfill the goal of the 3Rs.